Comparison of outcome and toxicity of postoperative intensity‐modulated radiation therapy with two‐dimensional radiotherapy in patients with soft tissue sarcoma of extremities and trunk - Jianyang Wang; Yongwen Song; Xinfan Liu; Jing Jin; Weihu Wang; Zihao Yu; Yueping Liu; Ning Li; Hui Fang; Hua Ren; Yuan Tang; Yu Tang; et al. (Cancer Medicine)
Abstract Background To compare the survival outcomes and late toxicities of postoperative intensity‐modulated radiation therapy (IMRT) with two‐dimensional radiotherapy (2D‐RT) for patients with soft tissue sarcoma (STS) of extremities and trunk. Methods 274 consecutive patients with nonmetastatic STS of extremities and trunk treated with postoperative IMRT (n = 187) and 2D‐RT (n = 87) were analyzed. Survival was calculated by using Kaplan‐Meier method. Independent prognostic factors were identified using Cox stepwise regression analysis for variables with a P‐value <0.1 in univariate analysis. Results With a median follow‐up time of 58.1 months, 30 local recurrences, 66 distant metastases, and 40 deaths occurred. Compared to 2D‐RT group, the IMRT group had higher 5‐year local recurrence‐free survival (LRFS) (91.1% vs 80.8%; P = 0.029), distant metastasis‐free survival (DMFS) (80.0% vs 69.7%; P = 0.048), disease‐free survival (DFS) (75.2% vs 59.2%; P = 0.021), and overall survival (OS) (90.2% vs 81.0%; P = 0.029). Multivariate analysis showed IMRT was an independent favorable factor for LRFS, DMFS, DFS, and OS. For late toxicities, the patients in IMRT group enjoyed lower incidences of ≥Grade 2 joint stiffness (3.9% vs 12.3%; P = 0.041) and ≥Grade 3 fractures (0.0% vs 3.4%; P = 0.25) than those in 2D‐RT group. ≥Grade 2 Edema was similar between these two groups (4.8% vs 9.2%; P = 0.183). Conclusions When compared with conventional techniques, postoperative IMRT seems to provide better LRFS, DMFS, DFS, and OS and less late toxicities in patients with STS of extremities and trunk, which should be offered as a preferred treatment.